ANALYSIS OF POTENTIAL HAZARDS IN MACHINE MAINTENANCE USING THE JOB SAFETY ANALYSIS (JSA) METHOD : CASE STUDY PT XYZ - Arista, Tipani; Fitriani, Fitriani; Fadillah, Mardi; Farisni, Teungku Nih; Siahaan, Perry Boy Chandra (HEARTY, 2025)
The increasing number of work accidents has recently become a global issue, especially in the cement industry. Work accidents occur due to potential hazards and potential risks in the workplace, this is a serious problem that can have an impact on worker safety and health, productivity, and operational efficiency of the company. Therefore, identification of potential hazards and control needs to be done to reduce or even eliminate the potential for work accidents and occupational diseases. This study aims to analyze and identify potential hazards and control potential hazards in machine maintenance work at the Rawmill Unit of PT XYZ using the Job Safety Analysis (JSA) method. This research is a qualitative research with a case study approach using the Job Safety Analysis (JSA) method. By using purposive sampling technique, a total of 4 informants were obtained. The data collection techniques used are observation and interviews. Data analysis used is semi-quantitative based on (AS/NZS 4360: 2004). Based on the results of the study, it is known that each stage of machine maintenance work has varying potential hazards. Through the hazard identification process, five categories of hazard factors were found, namely physical, chemical, biological, ergonomic, and psychological hazards, with a total of 31 identified hazard sources. The risk assessment results show that there are 18 potential risks at a high risk level (High Level) or 58%, 7 potential risks at a medium level (Medium Level) of 23%, and 6 potential risks at a low level (Low Level) of 19%. The most dominant potential hazards in machine maintenance work include the hazards of being pinched, crushed, electrocuted, exposed to welding flares, bumped, exposed to dust, exposed to chemicals, and broken tools that can hit the worker's body. The recommendations for control efforts that can be made are based on the control hierarchy, namely Substitution, Engineering Control, Administrative Control, and Personal Protective Equipment (PPE).